Stress Dynamics in Badminton Officials Through Heart Rate Variability Cognitive Load and Coping Mechanisms - Kumar P; Ravinder Pal Ahlawat; Jaiprakash Bhukar; Parveen Kumar; Sandeep Dhull; Gajender Singh; Ajithkumar L; Kasthuri Thilagam P (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: Badminton officials play a crucial role in ensuring fair play and accurate decision-making during competitions. However, officiating tasks are performed under high cognitive demands, time pressure, and social stressors, which can influence physiological responses and cognitive performance. Empirical evidence examining stress dynamics in badminton officials using objective physiological indicators remains limited. Methods: This study employed a descriptive repeated-measures design involving 102 certified badminton officials during a national-level competition. Heart rate data were recorded across five conditions: early morning rest, sitting near the referee table, during game intervals, between matches, and after competition. Data were analyzed using descriptive statistics, repeated-measures ANOVA, and Bonferroni post-hoc tests to identify differences in physiological responses across officiating situations. Result: Heart rate values increased progressively from resting conditions to peak levels during game intervals and between matches, indicating heightened physiological stress, before decreasing after the competition. Significant differences were observed across all measurement conditions (p < .001). Key stressors included spectator noise, high cognitive load, time pressure, and interpersonal and organizational demands. Elevated arousal levels suggested delayed physiological recovery during continuous officiating duties. Conclusion: Badminton officiating is associated with substantial physiological stress, particularly during critical match phases. Sustained stress may negatively affect cognitive and emotional functioning. The findings highlight the importance of implementing effective coping strategies, such as controlled breathing, mindfulness, and structured recovery routines, to support officials’ performance, well-being, and long-term officiating capacity.